2006
DOI: 10.1063/1.2199977
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of several photoluminescence bands in hafnium and zirconium silicates induced by ultraviolet photons

Abstract: Two photoluminescence (PL) components with peaks around 2.8–3.0 and 3.8eV were induced in hafnium silicates by the irradiation of synchrotron radiation photons at 8.0eV, while two similar ones were induced in zirconium silicates around 2.7–3.0 and 3.8eV. By examining PL excitation spectra, PL decay characteristics, and vacuum-ultraviolet absorption spectra, it is assumed that the origin of the PL component around 2.7(2.8)–3.0eV is the same as that of the PL component around 2.7–2.9eV observed in hafnia and zir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…The spectrum exhibits a symmetric (when plotted vs. photon energy) band between 1.8 and 3.3 eV, with a peak at 2.56 eV. Published investigations of short-time PL in HfO 2 films have reported emission bands in the visible region with peak energies that lie in the range 2.2-3.2 eV and seem to depend on the film crystallinity and synthesis route [6][7][8][9]18]. The origin of this PL emission is uncertain; it has been attributed to radiative recombination at defect centers, such as O vacancies [7] and, more …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum exhibits a symmetric (when plotted vs. photon energy) band between 1.8 and 3.3 eV, with a peak at 2.56 eV. Published investigations of short-time PL in HfO 2 films have reported emission bands in the visible region with peak energies that lie in the range 2.2-3.2 eV and seem to depend on the film crystallinity and synthesis route [6][7][8][9]18]. The origin of this PL emission is uncertain; it has been attributed to radiative recombination at defect centers, such as O vacancies [7] and, more …”
Section: Resultsmentioning
confidence: 99%
“…8 23 recently, proposed that this emission is intrinsic to HfO 2 , rather than defect-induced [6]. The short-time decay of this PL emission has been measured by Ito et al [6,18], and they found that the decay has two components, with characteristic time scales of $ 10 and $ 100 ns. However, decays at times longer than 300 ns have not been reported.…”
Section: Tablementioning
confidence: 96%
“…The inten sity of the 2.7 eV peak increases 7 times at annealing in oxygen. Earlier, luminescence in the 2.7 eV band was observed in [16][17][18][19][20]. The 2.2 eV luminescence band was observed in hafnium oxide [19,20].…”
Section: Experimental Techniquementioning
confidence: 90%
“…Earlier, luminescence in the 2.7 eV band was observed in [16][17][18][19][20]. The 2.2 eV luminescence band was observed in hafnium oxide [19,20]. The 3.2 eV luminescence was also reported in [19], whereas the 3.7 eV emission band was observed in [20].…”
Section: Experimental Techniquementioning
confidence: 90%
“…PL spectra obtained for ZrO 2 -SiO 2 samples [39] presented the broad band corresponding to band E, with no other bands at longer wavelengths, on UV excitation. Other PL spectra obtained for zirconium silicates presented a band at 460 nm, considered as intrinsic of zirconia [40], with no other bands at longer wavelengths, on UV excitation. The emission bands observed corresponding to the host for the GX samples then correspond to defect levels found in ZrO 2 or YSZ as described above.…”
Section: Article In Pressmentioning
confidence: 99%